Evaluasi Penerapan Early Warning Score di Ruang Rawat Inap Dewasa - Megawati, Sri Wulan; Jundiah, Raden Siti; Khotimah, Nur Intan Hayati Husnul; Muliani, Rizki (Jurnal Keperawatan Muhammadiyah, 2021)
Early Warning Score (EWS) is one of the instruments used to assess the patient's physiological deterioration and is one of the assessments in hospital accreditation. The application of the EWS can predict patient outcomes in the form of mortality, length of stay, and re-hospitalization. The purpose of this study was to evaluate the application of EWS in the inpatient room. This study was a prospective observational cohort study of patients in adult wards (â‰¥16 years) over a while (1 month). The number of samples was 256 patients. The instruments used in this study were a demographic data questionnaire and an EWS observation sheet. Descriptive statistics were used for patient characteristics, and EWS monitoring documents. The results showed that 100% of the EWS sheet documentation was incomplete, if this examination sheet was not carried out correctly it would affect the subsequent patient handling and patient outcomes both related to illness and death. Monitoring and evaluation related to the implementation of the EWS are very much needed in the future for the improvement of hospital services as a whole. Keywords: Early Warning Score, Evaluation